Morphological and Crystallographic Characterization of Primary Zinc-Rich Crystals in a Ternary Sn-Zn-Bi Alloy under a High Magnetic Field - Lei Li; Chunyan Ban; Ruixue Zhang; Haitao Zhang; Minghui Cai; Yubo Zuo; Qingfeng Zhu; Xiangjie Wang; Jianzhong Cui (Crystals, 2017)
Due to the unique capacity for structural control, high magnetic fields (HMFs) have been widely applied to the solidification process of alloys. In zinc-based alloys, the primary zinc-rich crystals can be dendritic or needle-like in two dimensions. For the dendritic crystals, their growth pattern and orientation behaviors under HMFs have been investigated. However, the three-dimensional crystallographic growth pattern and the orientation behaviors of the needle-like primary zinc-rich crystals under a high magnetic field have not been studied. In this work, a ternary Sn-Zn-Bi alloy was solidified under different HMFs. The above-mentioned two aspects of the needle-like primary zinc-rich crystals were characterized using the Electron Backscattered Diffraction (EBSD) technique. The results show that the primary zinc-rich crystals are characterized by the plate-shaped faceted growth in three dimensions. They grow in the following manner: spreading rapidly in the {0001} basal plane with a gradual decrease in thickness at the edges. The application of HMFs has no effect on the growth form of the primary zinc-rich crystals, but induces their vertical alignment. Crystallographic analysis indicates that the vertically aligned primary zinc-rich crystals orient preferentially with the c-axis perpendicular to the direction of the magnetic field.